EVALUASI PROSES PREOPERASI PADA PASIEN SECTIO CAESARIA (SC) DI RS PKU MUHAMMADIYAH GOMBONG - wiarti handayani; Basirun al ummah; isma yuniar (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2010)
The several is natural procces that will be experience by pregnant mothers and normal condition to reveral natural way. This is choice one of the best but if there is medicindication although nonmedicthat have revelaled cause caesar operation pass away.The objective of research as to fine out how preoperation section caesaria (sc) patient procces for perficly and quality patient expectialy. The desaign use in the research observation descriptive with desain cross sectional. The sample was taken by using purposive sampling, to 32 respondent/patient. The data were analasy by using univarian description to final. The reseach was comparated date 21 Mei 2009 until 21 Juni 2009 at PKU Muhammadiyah Gombong Hospital. The research finding showed that get date in perficly preoperation section caesaria (sc) procces 53% is the best and 47% is the sufficient and quality preoperation sc 57% is the best and 43% is sufficient. It could be concluded is evaluation preoperation section caesaria patient procces at PKU Muhammadiyah Gombong Hospital was got perfectly and quality preoperation is the best. Key words: sectio caesaria patient, preoperation, quality, and perficly